Study on pressure relief effect of multiple mining of protective layer in medium and long distance coal seam group - Xiapeng ZHANG; Kai WANG; Aitao ZHOU; Kequan YI; Zefan LI; Kejia WANG (Meikuang Anquan)
Aiming at the problem that the effect of protective layer mining of medium and long distance coal seam group under complex conditions is not clear, this study takes the coal seam group mining of Shanxi Xinjing Coal Mine as the engineering background, and uses the method of numerical simulation and physical similarity simulation to study the multiple pressure relief effect of medium and long distance coal seam group under the downward mining sequence. The evolution law of mining stress and movement deformation of protected layer is analyzed, and the pressure relief effect of protective layer mining is verified by field test. The numerical simulation results show that when the working faces of 8#, 9# and 15# coal seams advanced to 110 m, the minimum stress concentration coefficients of the coal body in front of the working face are 0.36, 0.25 and 1.30, respectively. After the completion of 3# coal seam mining, the maximum expansion deformation of 8# and 9# coal seam is 165.4 mm and 57.8 mm respectively, and the maximum expansion deformation of 15# coal seam is only 11.4 mm after the completion of 9# coal seam mining. The results of similar simulation experiments show that when the working face is advanced to 190 m, the stress concentration factors in front of 8#, 9# and 15# coal seams are 0.90, 0.84 and 1.14, respectively. The superimposed pressure relief effect caused by multiple mining of the protective layer of the coal seam group makes the displacement field of the overlying strata appear obvious superimposed changes. The maximum subsidence of the 3# coal seam roof increases from 0.51 m under primary mining to 1.16 m under tertiary mining. The results of the numerical simulation and similar simulation show that in the process of downward mining, the mining of the protective layer 3# and 8# coal seams has a significant pressure relief effect on the lower protected layer, while the 15# coal seam is basically not affected by the multiple mining pressure relief of the upper 3#, 8# and 9# coal seams. The results of field investigation and test show that after the mining of 3109 working face, the maximum pressure relief ratios of 8# and 9# coal seams reach 35.65% and 21.59% respectively, and the corresponding maximum relative deformation is 10.31‰ and 5.73‰ respectively.